Management strategies for perioperative anaemia in the severely burn-injured Jehovah's Witness patients who decline a blood transfusion: A systematic review with illustrative case reports. Issue 3 (May 2023) - Jung, Mia; Harish, Varun; Wijewardena, Aruna; Kerridge, Ian; Gillies, Rowan
Abstract: Background: The management of severe burn-injured Jehovah's Witness patients who decline a blood transfusion poses unique challenges. The literature is scant for guiding perioperative anaemia management in these patients. We present a systematic review of this patient group, along with illustrative, consecutive case reports of our experience. Methods: A systematic review was performed on Embase, MEDLINE and PubMed databases on articles discussing the treatment of burn-injured Jehovah's Witness patients. Articles were excluded if discussing isolated inhalation injury, or if blood transfusions were permitted. Results: Nine articles including a total of 11 patients revealed consistent themes. A multimodal medical and surgical approach is suggested. Medical strategies are directed at reducing blood loss and optimising haematopoiesis and include rationalising blood collection, reversing coagulopathy, administering tranexamic acid and regular erythropoietin. Surgical strategies include staged aggressive debridement, tumescent adrenaline infiltration and limb tourniquets. We found that the argon beam coagulator was an effective haemostatic adjunct not previously described in literature. Discussion: Management of anaemia in severely burn-injured Jehovah's Witness patients is challenging. This systematic review presents a summary of strategies directed at minimising blood loss, and optimising haematopoiesis. Careful preoperative planning, meticulous surgical technique, and postoperative physiological support are caveats to success. Highlights: There is no consensus on management of anaemia in burn injured Jehovah Witnesses. This review emphasises a multimodal approach to pre-, intra- and postoperative care. Medical strategies include optimising haematopoiesis with erythropoietin. Surgical strategies include fascial excision and argon beam coagulator haemostasis. We present a suggested treatment algorithm for burn-injured Jehovah's Witnesses.